(untitled) (Journal of Applied Learning and Teaching, 2019)
Despite increasing demands in the labour market for higher-order thinking skills, along with OECD reports highlighting an urgent need for a curriculum reform in the crisis-ridden country that will aim to adopt a more holistic approach to the education and development of its young people, Greece is still ranking among the lowest across 30 OECD countries in terms of performance on 21st century competencies, such as creativity, while also performing well below average on foundational literacies such as scientific and cultural and civic literacy. It should be hardly surprising that the structural constraints imposed by a debt-ridden economy seem to weigh heavily on the administrators, who, recognising the need for the nation to play catch-up, are currently amidst a curricular reform for a number of secondary school subjects, yet inevitably pushing over 500 of the most marginalised primary schools operating in rural and socioeconomically challenged parts of the country down the list of priorities. It is against this very backdrop, then, that questions such as “How can we do more with less?” have greater currency than ever. This ongoing scholarship investigates the design of a targeted intervention aiming to provide support for the more disadvantaged state schools where there is currently no provision for the teaching of English as a Foreign Language (EFL) due to geographical and budgetary constraints. ‘Self-organised learning’ as an alternative, cost-effective model for the enactment of the primary English curriculum to current approaches has been put to the test. Pupils from eight such schools participated in a quasi-experiment consisting of weekly sessions where they were encouraged to self-organise, take responsibility for the direction of their own learning, demonstrate initiative, and collaborate effectively. Preliminary findings are discussed in terms of behavioural changes regarding the above-mentioned skills, including the participants’ preparedness to self-direct.